Kanamycin-Mediated Conformational Dynamics of Escherichia coli Outer Membrane Protein TolC - Pattanayak, Biraja S.; Dehury, Budheswar; Priyadarshinee, Mamali; Jha, Suman; Beuria, Tushar K.; Soren, Dhananjay; Mallick, Bairagi C. (Frontiers in Molecular Biosciences, 2021)
TolC being a member of the outer membrane efflux proteins (OEPs) family, it acts as an exit duct to export proteins, antibiotics and substrate molecules across the Escherichia coli cell membrane. Export of these molecules is evidenced to be brought through the reversible interactions and binding of substrate-specific drug molecules or antibiotics with TolC and open for transport, whcih afterwards leading to cross-resistance. Hence, the binding study of kanamycin with TolC was monitored through molecular docking (MD) and the structural fluctuations and conformational changes to the atomic level was confirmed through the molecular dynamic simulation. The result was supported from the steady-state fluorescence binding and isothermal titration calorimetry (ITC) studies. Binding of kanamycin with TolC was resulted a concentration dependence fluorescence intensity quenching with 7 nm blue shift. ITC binding data upkeeps a single binding site endothermic energetic curve with binding parameters indicates an entrophy driven binding process. The confirmational changes resulting from this binding was monitored by circular dichroism (CD) study and the results shows insignificant changes in the -helix and -sheets secondary structure contents, but the tertiary structure shows inclusive changes in the presence of kanamycin. Which substaintial to corelate the RMSD, Rg and RMSF results. The resulting conformational changes of the TolC-kanamycin complexation was stabilized through H-bonding and other interactions.